Estudo de manobras evasivas com perturbações orbitais - Sousa, Rafael Ribeiro de [UNESP] (2015)
We studied the problem of the viability of space missions in debris environment space. Generally, a space vehicle in collision course with a space debris is destroyed or damaged and has impaired their mission. The preservation of these missions depends on the satellite capacity to avoid the collision, for example by an orbital maneuver known as evasive maneuver. In this study, we established strategies evasive maneuvers performed by a satellite via a propulsion system, whose efficiency is measured by technological parameters. Technological parameters are set in the planning of the mission, and describe the amount of fuel on board and the ability to expel propellant propulsion system. The evasive maneuvers were studied to be applied in such a way that the satellite escape the space debris without evasion of its nominal orbit mission, and for this purpose, include a propulsion control and treat the propulsion system as a disturbance in the orbit of satellite. It has also been established, to perform evasive maneuvers driven, propulsion which is connected at a fraction of the total time available for the maneuver. This fraction of time is defined as a propulsion pulse time. The evasive maneuvers are studied by numerical simulations of the dynamics of a debris and a vehicle space under the action of the Earth's gravitational and orbital perturbations arising from a propulsion system and the Earth's atmosphere. In these simulations calculate the debris of the collision conditions and the satellite, which occur around the Earth, and used to create technological parameters catalogs accessible to the satellite to escape these collisions